Determinants of lending interest rates of commercial banks in Kenya - Kananu, Elizabeth (Meru: Elizabeth Kananu, 2015)
The high interest rates charged by many commercial banks have attracted the attention of policy makers throughout the world. The commercial banks lending interest rates is a key indicator the marginal cost of short -term and long- term external funding in an economy and provides useful information about developments in the average cost of borrowing. This study investigates the determinants of lending interest rates commercial banks in Kenya. The objectives of this study this study was to establish the determinants of lending interest rate of commercial banks in Kenya. To achieve the objectives of the study, the researcher used regression analysis to establish the relationship between lending interest rates and the bank specific factors (bank size, market share and operational cost). The study adopted a descriptive research design. Descriptive research is the investigation in which quantity data will be collected and analyzed in order to describe the specific phenomenon in its current trends, current events and linkages between different factors in the current time. Descriptive research design was chosen because it enabled the researcher to establish a relation between variables. The study target population was the heads of credit department of 38 commercial banks in Kenya. Simple random sampling was used to select a sample size of 34 commercial banks of which the heads of credit department of these commercial banks were used for data collection.Primary data was collected by use of a semi-structured questionnaire distributed to the respondents and secondary data was collected fro CBK reports and banks financial report. The study was based 2013 annual data since most of the banks had their audited report released. The Statistical Package for Social Science (SPSS 17) was used for data presentation as done by the use of percentages and frequency tables. Pearson's product- moment correlation analysis and multivariate regression model to study the relationship between lending rate determinants (independent variables) and lending interest rate (dependent variable) was used.
Includes Index and Appendix